2014
DOI: 10.1097/mog.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, viruses, and intestinal immunity

Abstract: Purpose of review To highlight recent findings that identify an essential role for the cellular degradative pathway of autophagy in governing a balanced response to intestinal pathogens and commensals. Recent findings Following the genetic association of autophagy with inflammatory bowel disease (IBD) susceptibility, increasing evidence indicate that this pathway functions in various epithelial lineages to support the intestinal barrier. New studies are also revealing that autophagy proteins dictate the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…Dysfunction of autophagy has been associated with a number of inflammatory diseases (reviewed in ). Different mechanisms have been proposed to account for those associations.…”
Section: Autophagy and Autoimmune Diseasementioning
confidence: 99%
“…Dysfunction of autophagy has been associated with a number of inflammatory diseases (reviewed in ). Different mechanisms have been proposed to account for those associations.…”
Section: Autophagy and Autoimmune Diseasementioning
confidence: 99%
“…Basal autophagy occurs in nearly all kinds of cells to maintain the homeostasis of amino acid pool ( 59 ). Autophagy is generally classified into three types: macroautophagy, microautophagy, and chaperone-mediated autophagy ( 60 , 61 ). During the process of microautophagy, lysosomal/vacuolar membranes invaginate so as to engulf intracellular components via a non-selective degradative mechanism ( 62 ).…”
Section: Autophagy and Ibdmentioning
confidence: 99%
“…Since then, additional genetic studies have uncovered multiple genetic variants in key components of all steps of the autophagic pathway in IBD patients (Figure 1) [1416]. There is some overlap in these autophagy-related genetic variants in both CD and UC; however, the majority of the identified variants are more strongly associated with ileal CD.…”
Section: Autophagy-related Genes Linked To Ibd Susceptibilitymentioning
confidence: 99%
“…Recent studies demonstrated that additional IBD risk genes, NOD2 and leucine rich repeat kinase 2 (LRRK2), play roles in Paneth cell lysozyme packaging and secretion as well, suggesting that this autophagic response is regulated by multiple IBD risk genes [31]. A link more direct link to human IBD was identified through studies of transgenic mice with reduced Atg16L1 expression that demonstrated a requirement for an additional environmental insult for the development of altered Paneth cell morphology and CD-like ileitis [14]. These findings suggest that dysfunctional autophagy in Paneth cells may contribute to IBD onset through induction of intestinal dysbiosis that sensitizes these individuals to environmental triggers of IBD.…”
Section: Processes Affected By Dysfunctional Autophagy In Ibdmentioning
confidence: 99%
See 1 more Smart Citation